2015
DOI: 10.1089/ars.2015.6307
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Systemic Glucocerebrosidase Inhibition Induces Brain α-Synuclein Aggregation, Microglia and Complement C1q Activation in Mice

Abstract: Aims: Loss-of-function mutations in GBA1, which cause the autosomal recessive lysosomal storage disease, Gaucher disease (GD), are also a key genetic risk factor for the α-synucleinopathies, including Parkinson's disease (PD) and dementia with Lewy bodies. GBA1 encodes for the lysosomal hydrolase glucocerebrosidase and reductions in this enzyme result in the accumulation of the glycolipid substrates glucosylceramide and glucosylsphingosine. Deficits in autophagy and lysosomal degradation pathways likely contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 68 publications
8
111
0
Order By: Relevance
“…Overall, our data showing a therapeutic effect of GBA1 gene therapy on -synucleinopathy are not surprising given that reduced levels of GCase results in the accumulation of oligomeric and aggregated forms of -synuclein (Mazzulli et al, 2011;Osellame et al, 2013;Rocha et al, 2015b;Sardi et al, 2011;Sardi et al, 2013). Furthermore, a recent study demonstrates that systemic exposure to a GCase pharmacological chaperone in ASO mice diminishes behavioral deficits, reduces substantia nigra -synuclein aggregates, and decreases -synuclein immunoreactivity within dopamine neurons (Richter et al, 2014).…”
Section: Overexpression Of Gcase Protected Dopaminergic Neurons In Thsupporting
confidence: 56%
See 1 more Smart Citation
“…Overall, our data showing a therapeutic effect of GBA1 gene therapy on -synucleinopathy are not surprising given that reduced levels of GCase results in the accumulation of oligomeric and aggregated forms of -synuclein (Mazzulli et al, 2011;Osellame et al, 2013;Rocha et al, 2015b;Sardi et al, 2011;Sardi et al, 2013). Furthermore, a recent study demonstrates that systemic exposure to a GCase pharmacological chaperone in ASO mice diminishes behavioral deficits, reduces substantia nigra -synuclein aggregates, and decreases -synuclein immunoreactivity within dopamine neurons (Richter et al, 2014).…”
Section: Overexpression Of Gcase Protected Dopaminergic Neurons In Thsupporting
confidence: 56%
“…Diminished GCase activity can promote -synuclein aggregation in vitro and in vivo (Mazzulli et al, 2011;Sardi et al, 2011) and systemic administration of the GCase inhibitor, conduritol  epoxide, CBE, induces -synuclein aggregation in the substantia nigra of wildtype mice (Rocha et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…An appropriate animal model would greatly facilitate our understanding of this complicated relationship. Previous attempts at modeling GBA1- associated parkinsonism in the mouse used the inhibitor CBE, which inactivates GCase [16,18], but fails to represent the natural development of Parkinson disease, an age-related disorder. Studying L483P (L444P) mice over-expressing SNCA A53T , it was shown that the mutated GCase interfered with degradation and caused accumulation of SNCA in cultured primary neurons, although the mice had few symptoms [15].…”
Section: Discussionmentioning
confidence: 99%
“…Severe GBA1 mutations, such as loss of function mutations c.84insG and IVS2+1G > A, confer a higher risk for Parkinson disease and a more progressive course compared to milder mutations like N409S (N370S) [12,13]. Many groups have investigated the relationship between SNCA levels and GCase deficiency or inhibition, but only a few have utilized animal models [1417], including mice treated with the GCase inhibitor conduritol-β-epoxide (CBE) [16,18]. To further investigate the link between GBA1 mutations and Parkinson disease, we sought to develop an in vivo mouse model recapitulating the accelerated Parkinson disease course observed in loss-of-function GBA1 mutation carriers, by crossing a SNCA A53T transgenic mouse that develops severe motor impairment and neuronal SNCA inclusions [19], with heterozygotes for a functionally null gba allele [20].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, diminished GBA1 expression or GCase activity, exogenous introduction of GBA1 mutations or GC substrate enhance accumulation of α-syn while increased levels of α-syn decrease GCase protein and activity levels (93104). Therefore, therapies that augment GCase activity or decrease GlcCer accumulation could potentially have an impact on α-syn accumulation and aggregation and have a beneficial effect for patients with synucleinopathies.…”
Section: Expert Review and Five-year Viewmentioning
confidence: 99%